The Impact of Digital Content Marketing Strategies on Perceived Usefulness and VALORANT Game Acceptance - Nengah Sukendri; Zulfadli Ardiansyah; Agung Rizky; Asri Asri; Henry Zainarthur (ADI Publisher, 2025)
In the digital gaming industry that is becoming increasingly competitive, content marketing strategies play a crucial role in shaping players’ perceptions of a game’s quality and usefulness while influencing their decision to adopt it. As one of Riot games’ most prominent titles, VALORANT faces market dynamics that require digital marketing strategies that are informative, engaging, and sustainable. This study aims to analyze the influence of digital content marketing strategies on perceived usefulness and game acceptance using the Technology Acceptance Model (TAM) framework. The research employs a quantitative approach through an online survey of active VALORANT players, and the data are analyzed using Partial Least Squares Structural Equation Modeling (PLS-SEM) to examine causal relationships within TAM. The findings reveal that digital content marketing strategies have a significant positive effect on perceived usefulness, while Perceived Ease of Use (PEOU) also enhances Perceived Usefulness (PU) and overall game acceptance. Relevant and consistent content strengthens players’ perceived value, whereas ease of use supports a more comfortable and enjoyable gaming experience. This study highlights that strong digital content marketing strategies combined with a user-friendly game design are key factors in increasing player acceptance and engagement. The findings offer essential insights for developers and marketers in formulating effective content strategies to expand adoption, boost retention, and sustain the game’s community ecosystem.